Impact of an 8-week high-intensity bodyweight interval training on body composition and blood lipid metabolism in young women with overweight - Yamaner, Emre; Turğut, Tuna; Aksoy, Ayşe; Demirkıran, Burhan; Uçar, Mine Akkuş; Başoğlu, Burhan; Çamiçi, Furkan; Yanar, Muhammed Said; Bülbül, Alpay; Koç, Ahmet Ferdi; Ceylan, Tülay; Ceylan, Levent; et al. (Frontiers in Public Health, 2025)
BackgroundA physically inactive lifestyle is associated with an increased risk of obesity, dyslipidemia and metabolic disorders, especially in women. While high-intensity training methods have been extensively studied in male populations, the physiological and metabolic effects of high-intensity interval resistance training (HIIRT) in overweight women are understudied. The aim of this study was to investigate the effects of an 8-week HIIRT program on body composition and lipid metabolism in women.MethodsA total of 30 women (mean age: 23.13 ± 4.03 years, mean BMI: 31.21 ± 2.92 kg/m2) participated in an 8-week HIIRT program. Body composition was measured before and after the intervention using bioelectrical impedance analysis (BIA), while blood lipid parameters (triglycerides, total cholesterol, LDL, and HDL) were analyzed. Paired-sample t-tests were performed to determine the significance of the changes in body composition and lipid metabolism, using Cohen’s d effect size for interpretation.ResultsThe HIIRT program led to significant improvements in body composition, with body weight decreasing by 11.4 kg (p = 0.001, d = 0.96) and fat percentage decreasing by 3.1% (p = 0.001, d = 0.92). In addition, blood lipid profiles improved significantly, with triglycerides (−8.9 mg/dL, p = 0.001, d = 0.81, medium effect), total cholesterol (−19.7 mg/dL, p = 0,020, d = 1.98, large effect), and LDL (−8.2 mg/dL, p = 0.004, d = 1.96, large effect) decreased, while HDL increased by +10 mg/dL (p = 0.006, d ≥ 2.0, very large effect). These results underline the positive effects of HIIRT on lipid metabolism and cardiovascular health.ConclusionThe results suggest that HIIRT is an effective and time-efficient training model for improving body composition and metabolic health in women. The combination of high-intensity interval training principles with resistance exercise optimizes fat oxidation, improves fat metabolism and supports cardiovascular function. Given its efficacy, HIIRT could be a valuable strategy for treating metabolic disorders and reducing the risks of physically inactive behavior. Future research should focus on long-term adaptations and individual variability in metabolic responses to optimize HIIRT programs for broader populations.